Penangport together, we build a better future (Penang Port, 2013)
This book is a showcase on the milestones achieved by Penang Port Sdn Bhd, together with its management and staff. It also features the city of Penang which is recognized as a world heritage city. A melting port of cultures, Penang has always fascinated local and foreign tourists alike with it myriad of cultures from a multicultural society, variety of delicious foods incomparable to anywhere else in Malaysia and exotic sights and sounds from the combination of old and new infrastructure and architecture.